Artificial solid-liquid interface layer modified lithium metal electrode, preparation method and application thereof, and lithium metal battery
By constructing a high-density grain boundary structure ASEI layer on the surface of lithium metal, the problems of large crystal size and low grain boundary density in lithium metal batteries are solved, enabling rapid transfer and uniform deposition of lithium ions, and improving the cycle life and charge/discharge performance of the battery.
Patent Information
- Application Number
- CN202411349594.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
AI Technical Summary
In existing lithium metal batteries, the artificial solid-liquid interface layer (ASEI) has large crystal size, low grain boundary density, and high impedance, which leads to slow lithium-ion transfer rate, uneven dendrite growth, and shortened battery cycle life.
A high-density ASEI layer with grain boundary structure is constructed on the surface of lithium metal by coating the lithium metal surface with a modification liquid and allowing it to stand in a nitrogen atmosphere to generate an ASEI with high-density grain boundaries, including components such as lithium nitride, thereby increasing the grain boundary density and improving the lithium-ion transport rate.
It accelerates lithium-ion transfer, reduces ASEI impedance, inhibits dendrite growth, and improves the cycle life and rate performance of lithium metal batteries.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium metal electrode modified with an artificial solid-liquid interface layer, a preparation method and application thereof, and a lithium metal battery. Background Art
[0002] With the widespread popularity of electronic devices, electric vehicles and other fields, people's demand for high-efficiency and high-energy-density batteries is growing, so new battery technologies need to be developed to meet the above needs. Among them, lithium metal batteries have attracted much attention due to their higher energy density. In the lithium metal battery system, the gram capacity of lithium metal is as high as 3860mAh / g (11 times higher than graphite), and the redox potential is as low as -3.04V compared with the standard hydrogen electrode, which also means that its discharge voltage platform is higher. According to theoretical calculations, if the graphite negative electrode in the battery is replaced with lithium metal, the volume ED gain of the battery will increase by up to 62%, and the weight ED gain can increase by up to 45%, which means that at the same volume and weight, lithium metal batteries can store more energy, and electric vehicles, mobile phones and other devices will have longer battery life. However, in practical applications, lithium metal batteries face many challenges, such as impractical rate performance, unsafe cycle conditions and limited cycle life.
[0003] In related technologies, interface protection is one of the important strategies to stabilize lithium metal. Most researchers start from lithium metal materials and are committed to developing new artificial solid-liquid interfaces (ASEI) for modification to solve the above problems. However, the ASEI crystals prepared by conventional methods are large in size and have low grain boundary density. The impedance of ASEI is large, and the transfer of lithium ions from the electrolyte to the negative electrode surface requires overcoming a large energy barrier and a slow transfer speed. This also leads to uneven deposition of lithium ions at the negative electrode, which easily leads to disordered growth of dendrites and ultimately shortens the battery cycle life.
[0004] Therefore, it is of great significance to solve the current problems of large ASEI crystal size, low grain boundary density and high impedance, and to provide an artificial solid-liquid interface modification that can effectively accelerate the transfer speed of lithium ions and reduce ASEI impedance, so as to inhibit dendrite growth and thus improve the battery cycle life. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a lithium metal electrode modified with an artificial solid-liquid interface layer, a preparation method and application thereof, and a lithium metal battery, aiming to solve the problems of large ASEI crystal size, low grain boundary density, and high impedance in the current lithium metal electrode materials.
[0006] In the first aspect of the present invention, a lithium metal electrode is proposed, comprising metallic lithium and an artificial solid-liquid interface layer modified on the surface of the metallic lithium; the composition of the artificial solid-liquid interface layer includes N element, and one or more of Zr element, F element, P element, and S element; the grain size range of the artificial solid-liquid interface layer is 10 to 18 nm; the impedance range of the artificial solid-liquid interface layer is 30 to 100 Ω.
[0007] According to the lithium metal electrode of the embodiment of the present invention, at least the following beneficial effects are achieved: the lithium metal electrode provided by the present invention is modified with an artificial solid-liquid interface (ASEI) layer on the surface of metallic lithium, and the ASEI has the characteristics of a high-density grain boundary structure. The grain boundary is the interface between grains with different structures or orientations. On the crystal interface, the atomic arrangement transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state and has irregularity. This irregular grain boundary is an important channel for lithium ions to cross ASEI and reach the lithium metal surface for reversible reactions when the lithium metal battery is charged and discharged: inside the crystal, the atoms are arranged regularly, and lithium ions mainly diffuse in the solid phase through vacancies and gaps in the lattice, and the rate is relatively slow; while the atoms at the grain boundaries are arranged irregularly, and there are many defects and vacancies. Lithium ions can use these defects and vacancies to achieve multi-dimensional diffusion at a faster rate. Therefore, in most cases, the transfer rate of lithium ions at the grain boundaries is much higher than that inside the crystal. The present invention constructs an ASEI with a high-density grain boundary structure on the surface of metallic lithium, accelerates the transfer speed of lithium ions by increasing the grain boundary density, improves the ionic conductivity of the lithium metal surface, reduces the impedance of ASEI, can effectively avoid the energy consumption of lithium ions crossing the grain boundary, induces more uniform lithium ion deposition to inhibit dendrite growth, and further realizes the charging and discharging requirements of lithium metal batteries with high rate and no lithium dendrites, and improves the cycle life.
[0008] In the present invention, the grain size of the artificial solid-liquid interface layer ranges from 10 to 18 nm, and the impedance ranges from 30 to 100 Ω. A decrease in grain size can increase the grain boundary density, and an excessively large grain size can reduce the grain boundary density, thereby reducing the migration rate of lithium ions. The present invention can provide a grain size as low as 10 nm. The smaller the impedance, the more favorable it is for lithium ion migration; the larger the impedance, the slower the migration rate of lithium ions in ASEI, which ultimately affects lithium metal deposition and cycle life. The impedance of ASEI provided by the present invention can be as low as 30 Ω.
[0009] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and Zr element, the ratio of the content of the Zr element to the content of the N element (Zr / N) ranges from 0.25 to 0.45.
[0010] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and F element, the ratio of the content of F element to the content of N element (F / N) ranges from 0.5 to 2.
[0011] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and P element, the ratio of the content of the P element to the content of the N element (P / N) ranges from 0.5 to 2.
[0012] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and S element, the ratio of the content of the S element to the content of the N element (S / N) ranges from 0.4 to 1.
[0013] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N and multiple elements among Zr, F, P, and S, the ratio of the total content of the multiple elements to the content of N is in the range of 0.25 to 2. For example, when the composition of ASEI includes N, Zr, F, P, and S, the range of (Zr+F+P+S) / N is 0.25 to 2.
[0014] In the present invention, the element ratio of ASEI products can be obtained by mapping test. When the solute is single, the range of Zr / N is 0.25-0.45, the range of F / N is 0.5-2, the range of P / N is 0.5-2, and the ratio of S / N is 0.4-1. When the solute is not single, the element content is related to the composition ratio of the solute, and the range of (Zr+F+P+S) / N is 0.25-2.
[0015] In some embodiments of the present invention, the composition of the artificial solid-liquid interface layer includes lithium nitride and one or more of lithium nitrate, zirconium oxide, lithium fluoride, lithium phosphate, lithium oxide, lithium dodecylbenzene sulfonate, and lithium hydroxide.
[0016] In a second aspect of the present invention, a method for preparing a lithium metal electrode modified with an artificial solid-liquid interface layer is provided, comprising the steps of:
[0017] S1. Under a protective gas atmosphere, applying a modification solution of a predetermined concentration to the surface of metallic lithium;
[0018] S2, after the solvent of the modification solution is completely volatilized, placing the metal lithium coated with the modification solution in a nitrogen atmosphere, and standing for a predetermined time at a predetermined temperature to obtain a lithium metal electrode modified with an artificial solid-liquid interface layer;
[0019] Wherein, the solute of the modification solution includes one or more of zirconium oxynitrate, ammonium fluoride, phosphoric acid, and dodecylbenzene sulfonic acid.
[0020] According to the preparation method of the artificial solid-liquid interface layer modified lithium metal electrode of the embodiment of the present invention, at least the following beneficial effects are achieved: The present invention proposes an artificial solid-liquid interface (ASEI) modification method for lithium metal electrode: in a protective gas atmosphere, a quantitative modification liquid is applied to the surface of metal lithium, after the modification liquid solvent is completely volatilized, the metal lithium is placed in a nitrogen atmosphere, and is allowed to stand in a certain temperature environment, and finally a lithium metal electrode coated with ASEI is obtained, and the ASEI has the characteristics of a high-density grain boundary structure. The grain boundary is the interface between grains with different structures or orientations. On the crystal interface, the atomic arrangement transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state and has irregularity. This irregular grain boundary is an important channel for lithium ions to cross ASEI and reach the lithium metal surface for reversible reactions during the charging and discharging of lithium metal batteries: inside the crystal, the atoms are arranged regularly, and lithium ions mainly diffuse in the solid phase through the vacancies and gaps in the lattice, and the rate is relatively slow; while the atoms at the grain boundary are arranged irregularly, and there are many defects and vacancies, and lithium ions can use these defects and vacancies to achieve multi-dimensional diffusion, and the rate is faster. Therefore, in most cases, the transfer rate of lithium ions at the grain boundary is much higher than that inside the crystal. Therefore, the method provided by the present invention constructs a high-density grain boundary structure ASEI on the surface of metallic lithium, accelerates the transfer rate of lithium ions by increasing the grain boundary density, improves the ionic conductivity of the lithium metal surface, reduces the impedance of ASEI, can effectively avoid the energy consumption of lithium ions crossing the grain boundary, induces more uniform lithium ion deposition, and inhibits dendrite growth, thereby achieving high-rate, lithium dendrite-free lithium metal battery charging and discharging requirements and improving cycle life.
[0021] In some embodiments of the present invention, the solute of the modification solution includes one or more of zirconium oxynitrate, ammonium fluoride, phosphoric acid, and dodecylbenzenesulfonic acid (DBSA), preferably zirconium oxynitrate.
[0022] In some embodiments of the present invention, the solvent of the modification solution includes one or more of dimethyl sulfoxide (DMSO), ethylene carbonate (EC), ethyl methyl carbonate (EMC), acetonitrile (ACN), and methanol.
[0023] The components of ASEI generated by the present invention are mainly inorganic crystal materials, and according to the different formulas of the modification solution (solute+solvent), the main components of ASEI can include one or more of lithium nitrate, zirconium oxide, lithium fluoride, lithium phosphate, lithium oxide, lithium dodecylbenzene sulfonate, and lithium hydroxide in addition to lithium nitride. The solute of the modification solution is preferably zirconium oxynitrate, because zirconium oxynitrate reacts with lithium metal to form a variety of compounds, including a large amount of lithium nitride (Li3N), which has extremely high ionic conductivity, is conducive to the rapid transfer of lithium ions during the deposition and stripping process, and reduces the charge transfer impedance. Therefore, compared with other solutes, the ASEI generated by zirconium oxynitrate is conducive to reducing the charge transfer impedance and can show a lower SEI impedance in electrical properties.
[0024] In some embodiments of the present invention, the grain size of the artificial solid-liquid interface layer ranges from 10 to 18 nm, and the impedance ranges from 30 to 100 Ω. A decrease in grain size can increase the grain boundary density, and an excessively large grain size can reduce the grain boundary density, thereby reducing the migration rate of lithium ions. The present invention can provide a grain size as low as 10 nm. The smaller the impedance, the more favorable it is for lithium ion migration; the larger the impedance, the slower the migration rate of lithium ions in ASEI, which ultimately affects lithium metal deposition and cycle life. The impedance of ASEI provided by the present invention can be as low as 30 Ω.
[0025] In some embodiments of the present invention, the composition of the artificial solid-liquid interface layer includes lithium nitride, and one or more of lithium nitrate, zirconium oxide, lithium fluoride, lithium phosphate, lithium oxide, lithium dodecylbenzene sulfonate, and lithium hydroxide.
[0026] In the present invention, the element composition of ASEI varies according to the different solutes of the modification solution in the preparation process, wherein the characteristic elements in zirconium oxynitrate are Zr and N, ammonium fluoride is F, phosphoric acid is P, and dodecylbenzene sulfonic acid is S, and these characteristic elements will remain on the surface of lithium metal in the form of compounds after preliminary treatment. When the lithium metal after preliminary treatment is placed in a nitrogen atmosphere, lithium nitride will be generated on the surface of the lithium metal, and the content of N element will increase.
[0027] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and Zr element, the ratio of the content of the Zr element to the content of the N element (Zr / N) ranges from 0.25 to 0.45.
[0028] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and F element, the ratio of the content of F element to the content of N element (F / N) ranges from 0.5 to 2.
[0029] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and P element, the ratio of the content of the P element to the content of the N element (P / N) ranges from 0.5 to 2.
[0030] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N element and S element, the ratio of the content of the S element to the content of the N element (S / N) ranges from 0.4 to 1.
[0031] In some embodiments of the present invention, when the composition of the artificial solid-liquid interface layer includes N and multiple elements among Zr, F, P, and S, the ratio of the total content of the multiple elements to the content of N is in the range of 0.25 to 2. For example, when the composition of ASEI includes N, Zr, F, P, and S, the range of (Zr+F+P+S) / N is 0.25 to 2.
[0032] In the present invention, the element ratio of ASEI products can be obtained by mapping test. When the solute is single, the range of Zr / N is 0.25-0.45, the range of F / N is 0.5-2, the range of P / N is 0.5-2, and the ratio of S / N is 0.4-1. When the solute is not single, the element content is related to the composition ratio of the solute, and the range of (Zr+F+P+S) / N is 0.25-2.
[0033] The ratio of elements can intuitively reflect the degree of reaction of the previous and next processes, that is, the composition of ASEI. Take Zr / N as an example: the first process will generate LiZrO(NO3)2, and the Zr / N at this time is theoretically 0.5; the second process will generate Li3N on the surface of lithium metal. As the degree of reaction deepens, the ratio of Zr / N will decrease. When the Zr / N ratio is too high, it means that the degree of reaction in the second process is low. When the Zr / N ratio is too low, it means that the surface of lithium metal is covered with a large amount of Li3N. In both cases, a good high-density grain boundary structure cannot be formed. The same is true for the ratios of F / N, P / N, S / N and (Zr+F+P+S) / N. A high-density grain boundary structure can only be formed within a suitable range.
[0034] In some embodiments of the present invention, the concentration of the modification solution is 0.02% to 0.2% (wt%), preferably 0.05 to 0.15wt%, and more preferably about 0.1wt%. The modification solution used in the present invention is a low-concentration modification solution with a concentration of 0.02 to 0.2wt%. When the concentration is too low (lower than 0.02wt%), the modification effect cannot be achieved; when the concentration is too high, the surface of the metallic lithium will be completely covered by the generated inorganic salts, and it is impossible to provide active sites for the next step of the lithium metal and nitrogen reaction. In the present invention, in a dry protective gas atmosphere, the low-concentration modification solution in the above range is scraped onto the surface of the metallic lithium, and after the modification solution solvent is completely volatilized, the metallic lithium is placed in a nitrogen atmosphere and left to stand for several hours in a certain temperature environment, and finally, the lithium metal coated with ASEI can be obtained, and the ASEI has the characteristics of a high-density grain boundary structure.
[0035] In some embodiments of the present invention, the amount of the modification solution is 20 to 80 μL / cm 2 , preferably 40 to 60 μL / cm 2 , more preferably about 50 μL / cm 2 When the amount of modification liquid used is too low, the modification liquid cannot completely wet the surface of the lithium metal, resulting in incomplete and uneven modification reaction; when the amount of modification liquid used is too high, the surface of the lithium metal will be completely covered by the generated inorganic salts, and it will not provide active sites for the next step of the reaction between lithium metal and nitrogen.
[0036] In some embodiments of the present invention, the metal lithium is also subjected to surface polishing before being coated with the modification solution. The metal lithium should be surface polished before modification to remove surface oxides, so that the modification effect can be better regulated by the modification solution and uncontrollable factors of the experiment can be reduced.
[0037] In some embodiments of the present invention, the coating method of the modification liquid is scraping, spraying, spin coating or other conventional coating methods, and it is only necessary to ensure that the modification liquid is evenly distributed on the modified surface. Preferably, scraping is used.
[0038] In some embodiments of the present invention, in step S1, the protective gas may be nitrogen or an inert gas (such as argon, etc.).
[0039] In some embodiments of the present invention, the predetermined temperature is 0 to 100°C, preferably 30 to 80°C, and more preferably about 50°C. Temperature has an important influence on the nitridation reaction of lithium metal. When the temperature is too low, the crystal size of the product lithium nitride is large, and it is difficult to construct ASEI with a high-density grain boundary structure; when the temperature is too high, lithium nitride will decompose, release nitrogen, and reduce lithium metal. Therefore, the present invention selects a standing temperature of 0 to 100°C.
[0040] In some embodiments of the present invention, the predetermined time is 1 to 12 hours, preferably 2 to 12 hours. When the standing time is too short, the lithium nitride generated by the reaction fails to completely cover the active sites of the lithium metal, and ASEI has structural defects. When the standing time exceeds 12 hours, the nitridation reaction is completed. Therefore, the present invention selects a standing time of 1 to 12 hours.
[0041] In some embodiments of the present invention, the metal lithium coated with the modification solution is placed in a high-purity nitrogen atmosphere. Preferably, the purity of the high-purity nitrogen is ≥ 99%.
[0042] In step S2 of the present invention, the metal lithium coated with the modification liquid is placed in a high-purity nitrogen atmosphere (purity ≥ 99%) for static treatment at a temperature of 0 to 100°C for 1 to 12 hours. Under this condition, the metal lithium reacts with nitrogen to form lithium metal nitride, namely lithium nitride (Li3N), and the chemical reaction equation is 6Li+N2→2Li3N, and the product is usually purple or red. This is mainly because the metal lithium has a strong reducibility, reacts with nitrogen to form lithium metal nitride, and finally forms lithium metal coated with a high-density grain boundary structure ASEI.
[0043] In the related art, there are also patents that attempt to prepare two or more grain boundaries to inhibit the growth of lithium dendrites, thereby improving the stability and cycle life of the lithium metal negative electrode, such as Chinese patent CN202311554323.0. However, the above scheme essentially wants to use lithium salt inorganics with high mechanical strength to construct a solid electrolyte layer to induce plastic deformation of dendrites to inhibit dendrite growth. Different from this, the present invention uses an in-situ modification method to obtain a high-density grain boundary, because only the in-situ modification method (that is, the solute of the modification solution needs to react with lithium metal) can the lithium salt and lithium metal be closely attached, and the obtained high-density grain boundary ASEI can effectively improve the ionic conductivity of the lithium metal surface, induce more uniform lithium ion deposition, and thus achieve high-rate, lithium dendrite-free lithium metal battery charging and discharging requirements. In view of the extremely high ionic conductivity of lithium nitride (10 - 3 S / cm), which is much higher than other lithium salts. The simple way to generate lithium nitride is to introduce nitrogen gas to react with lithium metal. Therefore, the present invention adopts the above technical solution, which is not only simple and convenient, but also obtains lithium metal coated with high-density grain boundary structure ASEI.
[0044] The third aspect of the present invention provides a use of a lithium metal electrode as described in any one of the above items or a lithium metal electrode obtained by the preparation method as described in any one of the above items in the preparation of a lithium metal secondary battery.
[0045] In a fourth aspect of the present invention, a lithium metal battery is provided, comprising a lithium metal electrode as described in any one of the above items or a lithium metal electrode obtained by the preparation method as described in any one of the above items.
[0046] In some embodiments of the present invention, the lithium metal electrode is used as the negative electrode. After being assembled into a battery, the above electrode as the negative electrode can show higher rate performance and longer cycle life, and has extremely broad application prospects in the field of secondary batteries.
[0047] In some embodiments of the present invention, the lithium metal battery further comprises a positive electrode, a separator and an electrolyte.
[0048] Since the lithium metal battery (LMB) adopts all the technical solutions of the lithium metal electrode modified by the artificial solid-liquid interface of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, that is, it effectively improves the ionic conductivity of the surface of the lithium metal negative electrode, induces more uniform lithium ion deposition, and then realizes the high-rate and lithium dendrite-free lithium metal battery charging and discharging requirements, and has extremely broad application prospects in the field of secondary batteries.
[0049] In some embodiments of the present invention, the material of the positive electrode can be oxygen, elemental sulfur, metal oxides, and other commonly used positive electrode materials for lithium metal batteries in the art, without any limitation.
[0050] In some embodiments of the present invention, the separator is disposed between the positive electrode and the negative electrode, and the electrolyte infiltrates the positive electrode, the negative electrode and the separator.
[0051] In some embodiments of the present invention, the material of the diaphragm includes at least one of polyethylene, polypropylene and polyvinylidene fluoride. In actual production, the material and structure of the diaphragm are not strictly limited, for example, it can be a multi-layer structure formed by stacking the above materials, or a single-layer structure formed by mixing the above materials, or a single-layer structure formed by a single material; as long as it can play the basic role of the diaphragm.
[0052] In some embodiments of the present invention, the electrolyte includes an electrolyte salt and an organic solvent. The electrolyte salt includes lithium hexafluorophosphate. The organic solvent includes at least one of a carbonate solvent and a carboxylate solvent.
[0053] In some embodiments of the present invention, the carbonate solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC).
[0054] In some embodiments of the present invention, the carboxylate solvent includes propyl propionate (PP).
[0055] In some embodiments of the present invention, in the electrolyte solution, the concentration of the electrolyte salt is 0.8 to 1.5 mol / L.
[0056] In some embodiments of the present invention, in the lithium-ion battery, the electrolyte has a retention capacity of 6.05 to 9.65 g / 5 Ah, for example, 7.2 to 7.95 g / 5 Ah.
[0057] In a fifth aspect of the present invention, a use of the above-mentioned lithium metal battery in an energy storage device, an electrical device or an electronic device is proposed. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is an equivalent circuit diagram of the EIS test of a lithium metal symmetric battery provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0059] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0060] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0061] In the description of the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. Unless otherwise specified, each reaction or operation step may be performed in sequence or not. Preferably, the reaction method of the present invention is performed in sequence.
[0062] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the art or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased commercially.
[0063] Example 1
[0064] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , surface polishing is performed in advance to remove surface oxides), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 2 hours, and finally lithium metal coated with ASEI of a high-density grain boundary structure is obtained. The main components of ASEI are lithium nitride, lithium oxide, lithium nitrate and zirconium oxide.
[0065] Example 2
[0066] In a dry argon atmosphere, 50 μL of 0.2 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , surface polishing is performed in advance to remove surface oxides), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 2 hours, and finally lithium metal coated with ASEI of a high-density grain boundary structure is obtained. The main components of ASEI are lithium nitride, lithium oxide, lithium nitrate and zirconium oxide.
[0067] Example 3
[0068] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , surface polishing is performed in advance to remove surface oxides), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 12 hours, and finally lithium metal coated with ASEI of a high-density grain boundary structure is obtained. The main components of ASEI are lithium nitride, lithium oxide, lithium nitrate and zirconium oxide.
[0069] Example 4
[0070] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , surface polishing is performed in advance to remove surface oxides), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 80°C for 2 hours, and finally lithium metal coated with ASEI of a high-density grain boundary structure is obtained. The main components of ASEI are lithium nitride, lithium oxide, lithium nitrate and zirconium oxide.
[0071] Example 5
[0072] In a dry argon atmosphere, 50 μL of 0.1 wt% ammonium fluoride / methanol modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , surface polishing is performed in advance to remove surface oxides), and after the solvent methanol is completely evaporated, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 2 hours, and finally lithium metal coated with ASEI with a high-density grain boundary structure is obtained. The main components of ASEI are lithium nitride and lithium fluoride.
[0073] Comparative Example 1
[0074] In a dry argon atmosphere, 100 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , the surface is polished in advance to remove the surface oxide), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 2 hours to finally obtain the lithium metal coated with ASEI.
[0075] Comparative Example 2
[0076] In a dry argon atmosphere, 50 μL of 0.3 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , the surface is polished in advance to remove the surface oxide), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 2 hours to finally obtain the lithium metal coated with ASEI.
[0077] Comparative Example 3
[0078] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , the surface is polished in advance to remove the surface oxide), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 50°C for 0.5 hours to finally obtain the lithium metal coated with ASEI.
[0079] Comparative Example 4
[0080] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , the surface is polished in advance to remove the surface oxide), and after the solvent dimethyl sulfoxide is completely volatilized, the lithium metal is placed in a nitrogen atmosphere and allowed to stand at a temperature of 120°C for 2 hours to finally obtain the lithium metal coated with ASEI.
[0081] Comparative Example 5
[0082] In a dry argon atmosphere, 50 μL of 0.1 wt% zirconium oxynitrate / dimethyl sulfoxide modification solution was scraped onto the surface of lithium metal (the surface area of lithium metal was 1 cm 2 , the surface is polished in advance to remove the surface oxide), and after the solvent dimethyl sulfoxide is completely volatilized, 50 μL of 0.1wt% ammonium fluoride / methanol modification solution is scraped on the surface of the lithium metal, and after the solvent methanol is completely volatilized, the lithium metal coated by ASEI is finally obtained.
[0083] Performance Testing
[0084] 1. Grain boundary density test
[0085] The distribution of inorganic crystal sizes on the modified lithium metal surfaces obtained in Examples 1-5 and Comparative Examples 1-5 was tested by TEM, and the testing method was as follows:
[0086] 1) After ASEI grows on the surface of lithium metal, a small amount of powder is scraped with a scraper, dispersed with a dispersant, and then ultrasonically prepared into a suspension;
[0087] 2) Dropping the suspension onto a support film and drying to obtain a sample;
[0088] 3) Perform TEM and HRTEM (high-resolution transmission electron microscopy) on the samples to observe the sample's lattice fringes, crystal size, grain boundaries and other structures.
[0089] The results are shown in Table 1. The observation and statistical results show that the ASEI in the embodiment has a higher density of grain boundaries and a smaller internal crystal size.
[0090] 2. Lithium metal symmetric battery EIS test
[0091] The modified lithium metals obtained in Examples 1-5 and Comparative Examples 1-5 were cut into 16 mm small discs, and two identical small discs were used to assemble a 2032 symmetrical battery, wherein the electrolyte formula was 1M LiPF6 EC / EMC electrolyte, EC:EMC=3:7, and the separator was a 14 μm thick PE separator. At the same time, a 2032 symmetrical battery prepared by the same steps using lithium metal without any treatment was used as Comparative Example 6.
[0092] An electrochemical workstation was used to perform EIS tests on the lithium metal symmetric batteries obtained in Examples 1-5 and Comparative Examples 1-6, and the impedance of RSEI, i.e., ASEI, was obtained by fitting the curves.
[0093] Among them, EIS test instrument: Shanghai Chenhua electrochemical workstation;
[0094] Test frequency: 10 -2 ~10 5 Hz;
[0095] The equivalent circuit diagram is as follows Figure 1 shown.
[0096] The results are shown in Table 1. The lower the RSEI, the higher the ionic conductivity. It was found that lithium metal with high-density grain boundary ASEI has higher ionic conductivity.
[0097] 3. Comparison of cycle life of lithium metal symmetric batteries
[0098] The modified lithium metals obtained in Examples 1-5 and Comparative Examples 1-5 were cut into 16 mm small discs, and two identical small discs were used to assemble a 2032 symmetrical battery, wherein the electrolyte formula was 1M LiPF6 EC / EMC electrolyte, EC:EMC=3:7, and the separator was a 14 μm thick PE separator. At the same time, a 2032 symmetrical battery prepared by the same steps using lithium metal without any treatment was used as Comparative Example 6.
[0099] The cycle life of the lithium metal symmetrical batteries obtained in Examples 1-5 and Comparative Examples 1-6 was compared, and the current density was set to 1 mAh / cm 2 , single charge surface capacity is 1mAh / cm 2 The battery is charged and discharged in a cycle at room temperature until the polarization voltage is greater than 0.5 V, and the cycle life of the symmetrical batteries of the embodiments and comparative examples is compared.
[0100] The testing process is as follows:
[0101] 1) Leave for 5 minutes;
[0102] 2) At 1 mAh / cm 2 The current is constant current charged for 1h;
[0103] 3) Leave for 5 minutes;
[0104] 4) At 1 mAh / cm 2 The current is discharged at a constant current for 1h;
[0105] 5) Repeat 1-4 until the polarization voltage is greater than 0.5V;
[0106] 6) End.
[0107] The test results are shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] It can be seen from the above examples 1-4 and comparative examples 1-2 that the amount and concentration of the modification solution mainly affect the amount of inorganic salts generated. When the amount or concentration is too high, the surface of the lithium metal will be completely covered by the inorganic salts generated, and it will not be able to provide active sites for the next step of the lithium metal and nitrogen reaction, so that the ASEI with a high-density grain boundary structure cannot be formed, which is manifested as an increase in the average crystal size and RSEI, a decrease in ionic conductivity, and a decrease in cycle life. If the concentration of the modification solution is too high, the thickness of the ASEI will increase, the migration path of lithium ions from the electrolyte to the negative electrode surface will become longer, and the migration rate will decrease, which will be manifested as an increase in RSEI in the impedance test and a decrease in life in the symmetrical battery test.
[0112] It can be seen from the above Examples 1-4 and Comparative Example 3 that the standing time in a nitrogen atmosphere mainly affects the generation of lithium nitride and the distribution of ASEI defects. When the standing time is too short, the lithium nitride generated by the reaction fails to completely cover the active sites of lithium metal, and ASEI has structural defects.
[0113] It can be seen from the above Examples 1-4 and Comparative Example 4 that the standing temperature also has an important influence on the nitridation reaction of lithium metal. When the standing temperature is too high, lithium nitride will decompose, release nitrogen and reduce lithium metal, that is, the nitridation reaction of lithium metal will not occur.
[0114] It can be seen from the above Example 5 that when the solute of the modification solution is changed from zirconium oxynitrate to ammonium fluoride, it can be found that RSEI increases significantly. This is because the lithium fluoride ion conductivity generated by the latter reacting with lithium metal is lower than that of lithium nitride; in Comparative Example 5, low concentrations of zirconium oxynitrate solution and ammonium fluoride solution are used to modify lithium metal respectively, and the lithium metal is not placed in a nitrogen environment and allowed to stand, which also causes RSEI to increase significantly. This is also due to the lack of lithium nitride with high ionic conductivity.
[0115] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A lithium metal electrode, characterized in that It comprises metallic lithium and an artificial solid-liquid interface layer modified on the surface of the metallic lithium; the composition of the artificial solid-liquid interface layer comprises N element and one or more of Zr element, F element, P element and S element; The grain size of the artificial solid-liquid interface layer ranges from 10 to 18 nm; The impedance range of the artificial solid-liquid interface layer is 30-100Ω.
2. The lithium metal electrode according to claim 1, characterized in that When the composition of the artificial solid-liquid interface layer includes N element and Zr element, the ratio of the content of Zr element to the content of N element is in the range of 0.25 to 0.45; And / or, when the composition of the artificial solid-liquid interface layer includes N element and F element, the ratio of the content of F element to the content of N element is in the range of 0.5 to 2; And / or, when the composition of the artificial solid-liquid interface layer includes N element and P element, the ratio of the content of P element to the content of N element is in the range of 0.5 to 2; And / or, when the composition of the artificial solid-liquid interface layer includes N element and S element, the ratio of the content of S element to the content of N element is in the range of 0.4 to 1; And / or, when the composition of the artificial solid-liquid interface layer includes N element and multiple elements of Zr element, F element, P element and S element, the ratio of the total content of the multiple elements to the content of N element is in the range of 0.25 to 2.
3. The lithium metal electrode according to claim 1 or 2, characterized in that The artificial solid-liquid interface layer is composed of lithium nitride and one or more of lithium nitrate, zirconium oxide, lithium fluoride, lithium phosphate, lithium oxide, lithium dodecylbenzene sulfonate, and lithium hydroxide.
4. A method for preparing a lithium metal electrode modified with an artificial solid-liquid interface layer, characterized in that: Includes steps: Under a protective gas atmosphere, applying a modification solution of a predetermined concentration to the surface of the metal lithium; After the solvent of the modification solution is completely volatilized, the metal lithium coated with the modification solution is placed in a nitrogen atmosphere and allowed to stand at a predetermined temperature for a predetermined time to obtain a lithium metal electrode modified with an artificial solid-liquid interface layer; Wherein, the solute of the modification solution includes one or more of zirconium oxynitrate, ammonium fluoride, phosphoric acid, and dodecylbenzene sulfonic acid.
5. The method for preparing a lithium metal electrode modified with an artificial solid-liquid interface layer according to claim 4, characterized in that: The concentration of the modification solution is 0.02-0.2 wt %; And / or, the amount of the modification solution is 20-80 μL / cm 2 ; And / or, the solvent of the modification solution includes one or more of dimethyl sulfoxide, ethylene carbonate, ethyl methyl carbonate, acetonitrile, and methanol.
6. The method for preparing a lithium metal electrode modified with an artificial solid-liquid interface layer according to claim 4, characterized in that: The predetermined temperature is 0 to 100° C. And / or, the predetermined time is 1 to 12 hours; and / or, placing the metallic lithium coated with the modification solution in a high-purity nitrogen atmosphere; Preferably, the purity of the high-purity nitrogen is ≥99%.
7. The method for preparing a lithium metal electrode modified with an artificial solid-liquid interface layer according to claim 4, characterized in that: The artificial solid-liquid interface layer is composed of lithium nitride and one or more of lithium nitrate, zirconium oxide, lithium fluoride, lithium phosphate, lithium oxide, lithium dodecylbenzene sulfonate, and lithium hydroxide.
8. Use of the lithium metal electrode according to any one of claims 1 to 3 or the lithium metal electrode obtained by the preparation method according to any one of claims 4 to 7 in the preparation of a lithium metal secondary battery.
9. A lithium metal battery, characterized in that: It comprises the lithium metal electrode as described in any one of claims 1 to 3 or the lithium metal electrode obtained by the preparation method as described in any one of claims 4 to 7.
10. Use of the lithium metal battery as claimed in claim 9 in an energy storage device, an electrical device or an electronic device.
Citation Information
Patent Citations
Negative electrode and preparation method thereof, battery and electric device
CN117476876A